New insights into the Ma‘agan Mikhael B shipwreck, Israel - Cohen, Maayan; Cvikel, Deborah (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The Ma‘agan Mikhael B ship was a lateen-rigged merchantman, about 23 m long, with an estimated displacement of 120 tons, dated to the mid-7th–mid-8th centuries AD. In six excavation seasons so far, from 2016 to 2019, the hull and the artefacts have been recorded underwater, and some of the latter were retrieved and studied on land. Based on its construction details – no planking edge-fasteners, and planks butt-jointed at frame stations – it appears that the ship was built to a ‘frame-based’ concept. It is thus among the earliest frame-based shipwrecks found to date in the eastern Mediterranean.